Attachment as Environmental Factor Influencing the Development of Externalizing and Internalizing Behaviors in Children with Atten-tional Déficit Hyperactivity Disorder - Moneta, Maria Eugenia; Rothhammer, Paula; Carrasco, Ximena (Journal of Psychology and Psychotherapy Research, 2016)
The current study aims at the relevance of parenting environment in the generation of co-morbid disorders in children diagnosed with Attention Déficit/ hyperactivity Disorder (ADHD). Although considerable evidence has demonstrated that ADHD has a biological and genetic basis, our work points towards family environment and attachment during development. We postulate that attachment style and mothers attitude towards the child early in development, have a role to play in the generation of co-morbid behavior. We demonstrated that school children experiencing insecure attachment patterns have higher proportion of co-morbid behaviors than secure children diagnosed with ADHD and controls. Results are discussed with regard to the role of environmental and family factors in the development of the illness and treatment course. These findings provide empirical evidence for the differential susceptibility to maternal (principal care person) influences in ADHD children, suggesting the importante of early interventions.